Carnival at candlelight - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2005)
While on a mission to prove to Merlin that they can use magic wisely, Jack and Annie travel to seventeenth-century Venice, Italy, to save the city from disaster.
"A Merlin mission."
"A Stepping Stone book."
Keywords: Time travel; Magic; Tree houses; Brothers and sisters